Low-Flow Arterialized Venous Malformations of the Orbit. Issue 4 (July 2017) - Callahan, Alison B.; Meyers, Philip M.; Garrity, James A.; Son, Jung H.; Petris, Carisa; Kazim, Michael
Abstract : Purpose: Orbital vascular malformations are classified by their hemodynamic properties, either high or low flow. Low-flow lesions may be simple venous, lymphatic, or combined lymphaticovenous malformations. The authors report a series of cases in which predominantly low flow, venous lesions were unexpectedly noted to have arterial feeders. Methods: A retrospective chart review of patients identified by the authors as having orbital varices with arterial components was conducted. The authors identified 7 such cases. After careful review, 2 cases were excluded due to inconclusive neuroradiographic findings. The authors review the clinical, radiologic, histopathologic, and surgical information from the remaining 5 cases and discuss their clinical significance. Results: All 5 cases were most consistent with variceal lesions: 3 as clinically distensible lesions and 2 as thrombosed lesions. Additional arterial feeder vessels were noted by angiography (3) or intraoperative visualization (2). The arterial contribution varied from faint vessels to distinct branches of the ophthalmic artery. Ages ranged from 13 to 61 years without predilection for gender. Treatments consisted of excision, embolization, and observation. Two poignant cases are highlighted: the first illustrating that an angiogram in isolation of its clinical picture can be misleading and result in treatment intervention with undue risk, and the second illustrating that inadequate treatment of unrecognized arterial components may contribute to recurrences. Conclusions: Low-flow orbital variceal lesions may have less prominent, arterial components. This type of combined arterialized venous malformation is largely unrecognized in the ophthalmic literature. Correct identification of these lesions is critical in providing safe, effective, and durable treatment. Abstract : Low flow, venous malformations of the orbit may have arterial feeder vessels; this type of low flow, combined arterialized venous malformation has yet to be clearly described in the orbit.